RASIONALISASI IDEOLOGI SUNDA WIWITAN (KABUYUTAN): PENYATUAN DIRI URANG SUNDA KEPADA GUNUNG SEBAGAI LAMBANG SEMESTA (KOSMIS) - Richadiana Kartakusuma (Berkala Arkeologi, 2006)
This paper presents the history of Sundanese culture in a holistic manner so that it is understood more deeply, not restricted to abstract concepts but to be more operational. With noting to the shortcomings and weaknesses that exist, the description of Sundanese culture rests on objective facts, easily understood with a systematic frame of mind so that the picture and meaning of Sundanese culture can be seen clearly.